Note on the dynamics of a slightly deformable body - Hemp, W. S. (College of Aeronautics, Cranfield, 1947)
The purpose of this note is to develop the equations of motion of a slightly deformable body. Appeal to general principles shows the independence of the translation (Para.2). Moving axis are defined in papa.3 which can be taken to define the rotation. Motion relative to these axes is described by normal co-ordinates (Para.4) and the kinetic energy of the motion relative to the centre of mass is split into two parts; the energy of rotation and the energy of vibration (Para.5). Equations for the vibration are then formulated (Para.6). Attention is drawn to the coupling between rotation and vibration, which only vanishes when the angular velocities are small (Para.7).